Comparison of selected parameters for evaluation of rail surface damage intensity - Jiří Šlapák; Tomáš Michálek (Acta Polytechnica CTU Proceedings)
This paper deals with the issue of evaluation of a rail surface damage (RSD) intensity. Some ways of calculating parameters that represent the RSD are described. In this context, a multi-body model of a railway vehicle was created and several simulations of this model on a curved track were performed. Furthermore, these simulations were evaluated and the RSD parameters were compared.